Schrödinger and the Possible Existence of Different Types of Life - Hernández, Greco (Frontiers in Microbiology, 2022)
Eighty years ago, Nobel Prize-winner physicist Erwin Schrödinger gave three lectures in Dublin´s Trinity College, titled What is Life? The physical aspect of the living cell, to explain life in terms of the chemistry and physics laws. Life definitions rely on the cellular theory, which poses in the first place that life is made up of cells. The recent discovery of giant viruses, along with the development of synthetic cells at the beginning of century 21st, has challenged the current idea of what life is. Thus, rather than having arrived at a close answer to Schrödinger´s question, modern biology has touched down at a novel scenario in which several types of life—as opposed to only one—actually might exist on Earth and possibly the Universe. Eighty years after the Dublin lectures, the Schrödinger question could be: “What are lives”?